Effect of L-leucine on p-aminohippurate accumulation by mammalian renal cortical slices - Kuo, Chao-Hen; Hook, Jerry B. (Biochimica et biophysica acta, 1979)
The effect of several amino acids (L-glutamate, L-phenylalanine, L-leucine, glycine, L-tryptophan, L-histidine, L-valine) on p-aminohippurate accumulation was evaluated in rat, mouse and rabbit kidneys. Only leucine was found to enhance p-aminohippurate accumulation in rat and mouse renal cortical slices but not in rabbit slices. Leucine had no effect on tetraethylammonium accumulation. In rat renal cortical slices, leucine increased the uptake and decreased the runout of p-aminohippurate, each effect contributing to the increase in p-aminohippurate accumulation. The apparent K m of p-aminohippurate uptake was decreased by leucine with no change in the apparent V. Aminooxyacetate (an inhibitor of transamination of leucine) partially depressed the stimulating effect of leucine on p-aminohippurate accumulation, whereas α-ketoisocaproic acid (a metabolite of leucine formed by transamination) enhanced p-aminohippurate accumulation, suggesting that the metabolism of leucine in kidney slices may be necessary for the stimulating effect on p-aminohippurate transport.